INFLUENCE OF OBESITY AND LIFESTYLE FACTORS ON FEMALE INFERTILITY: A STUDY AT KHYBER TEACHING HOSPITAL PESHAWAR - Dr Laila Hussain; Dr Sumbal Afridi; Dr Reema Fateh; Dr Farrukh Gul; Dr Yusra Ali; Dr Rahat Bibi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: There is growing recognition that obesity and other lifestyle determinants are essential causes of infertility in women. Increased prevalence of obesity in women of reproductive age is a health issue of concern to the general population, especially in less-developed and middle-income countries. Objective: To assess how obesity and lifestyle habits relate to infertility in women being treated in Khyber Teaching Hospital in Peshawar, and the metabolic and hormonal risk factors associated with this association. Methods: The present cross-sectional descriptive study was carried out at Gynae & Obs Department, MTI Khyber Teaching Hospital Peshawar, Pakistan from 1st January, 2025 to 30th June, 2025. Two hundred and fifty women between the ages of 18 and 45 years were recruited with primary or secondary infertility. Structured questionnaires, anthropometry, and laboratory measurements of BMI, waist circumference, insulin resistance, thyroid functionality, and reproductive hormones were used to collect the data. There was also testing of lifestyle factors such as diet, physical activity, smoking, and sleep. Results: 70 percent obesity, 40 percent insulin-resistance. Imbalances in hormones and sedentary lifestyles were highly fashionable and directly related to infertility. Conclusion: The reproductive outcome should be improved by metabolic screening, lifestyle and general weight management.